BUILDING ENTREPRENEURIAL RESILIENCE: HOW INDONESIAN MSMEs NAVIGATE GLOBAL SUPPLY CHAIN DISRUPTIONS AND CLIMATE CHANGE CHALLENGES (Jurnal Teknologi Industri Pertanian, 2026)
Micro, small, and medium enterprises (MSMEs) in Indonesia play a significant role in advancing the Indonesian economy; however, they are vulnerable to challenges caused by climate change as a global consequence, as well as challenges stemming from global supply chain issues. In this regard, with a focus on rapid technological change and sustainability, MSMEs have considerable potential for transformation. With the above elaboration, this research aims to examine from the perspective of MSMEs in Indonesia the impact of entrepreneurial resilience and business sustainability on the adoption of green innovation, digital technology, diversified supply chains, and collaborative ecosystems. To address the aforementioned research questions, a quantitative approach using structural equation modelling (partial least squares) (PLS-SEM) was employed with a sample of 250 MSMEs from three provinces in Indonesia: West Java, Central Java, and North Sumatra. For model assessment, this assessment focused on (i) indicator weights, (ii) average variance extracted (AVE), and (iii) composite reliability. In this context, hypothesis testing was conducted using bootstrapping. In summary, digitization and supplier diversification were recorded for the first time as having a positive impact on entrepreneurial resilience, whereas green innovation has a significant yet negative influence on entrepreneurial resilience. Additionally, resilience was proven to have a positive effect on business sustainability. Within the framework of the entire model, the strength of explanation is impressive, reaching R² of 0.995 for entrepreneurial resilience and R² of 0.885 for business sustainability. The results show that several components of the internal adaptive capacity of MSMEs, in particular, digital transformation and flexible supply chain management, are vital for enhancing the resilience and sustainability of MSMEs in the long term, while the effects of green innovation and ecosystem collaboration appear to be more contextually contingent.Keywords: digital adoption, eco-innovation, resilience, supplier diversification, sustainability.